Capital as Power in the 21st Century. A Conversation - Michael Hudson; Jonathan Nitzan; Tim Di Muzio; Blair Fix (Review of Capital as Power, 2025)
On December 3, 2024, Michael Hudson met with capital-as-power researchers Jonathan Nitzan, Tim Di Muzio, and Blair Fix to discuss the intersections between their two lines of research. What follows is a transcript of the conversation. A recording of the discussion is available at https://www.youtube.com/watch?v=tBOU4xBg2pA.
Keywords: P; P1; P12; G; 330; capital accumulation; capital as power; capitalism; finance; political economy; philosophy of science; production; rent